2021
DOI: 10.5194/acp-21-9223-2021
|View full text |Cite
|
Sign up to set email alerts
|

Towards understanding the characteristics of new particle formation in the Eastern Mediterranean

Abstract: Abstract. To quantify the contribution of new particle formation (NPF) to ultrafine particle number and cloud condensation nuclei (CCN) budgets, one has to understand the mechanisms that govern NPF in different environments and its temporal extent. Here, we study NPF in Cyprus, an Eastern Mediterranean country located at the crossroads of three continents and affected by diverse air masses originating from continental, maritime, and desert-dust source areas. We performed 1-year continuous measurements of aeros… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 149 publications
3
19
0
Order By: Relevance
“…3D). While the background accumulation mode concentration is comparable to median April concentrations measured at land-based Arctic locations including mount Zeppelin (Svalbard), Villum research station at Station Nord (VRS; Greenland), Alert (Canada), Utqiagvik (Alaska) and Tiksi (Russia) (100-200 cm −3 ) 25,35 , concentrations during the intrusion period are similar to summer average accumulation mode particle concentrations observed in rural 36 and even urban 37 mid-latitude locations. This comparison shows the dramatic impact of the intrusion on the aerosol number size distribution in the remote Arctic.…”
Section: Aerosol Size Distribution Number and Mass Concentrationssupporting
confidence: 60%
“…3D). While the background accumulation mode concentration is comparable to median April concentrations measured at land-based Arctic locations including mount Zeppelin (Svalbard), Villum research station at Station Nord (VRS; Greenland), Alert (Canada), Utqiagvik (Alaska) and Tiksi (Russia) (100-200 cm −3 ) 25,35 , concentrations during the intrusion period are similar to summer average accumulation mode particle concentrations observed in rural 36 and even urban 37 mid-latitude locations. This comparison shows the dramatic impact of the intrusion on the aerosol number size distribution in the remote Arctic.…”
Section: Aerosol Size Distribution Number and Mass Concentrationssupporting
confidence: 60%
“…The intensity of solar radiation reaching the Earth's surface has been suggested as the most important factor in determining the onset of atmospheric NPF. However, the nighttime NPFs have also been reported at several locations (Baalbaki et al, 2021;Junninen et al, 2008;Kammer et al, 2018;Salimi et al, 2017) showing that chemical mechanisms that do not depend on photooxidation could also be responsible for the observed NPFs. Some studies have indicated the connection between the ambient temperature and relative humidity with the occurrence of NPF, albeit with different responses (with both positive and negative feedbacks) between different studies (see Kerminen et al, 2018 and references therein).…”
mentioning
confidence: 85%
“…Studies have shown the growth of the newly-formed particles followed by shrinkage in modal diameter (Alonso-Blanco et al, 2017;Hakala et al, 2019;Salma et al, 2016;Yao et al, 2010;Young et al, 2013;J. Zhang et al, 2016), the occurrence of two or more NPF events during the same day (Baalbaki et al, 2021;Hirsikko et al, 2013;Kyrö et al, 2013;Salma & Németh, 2019;Svenningsson et al, 2008), or the first detected particle mode over 10 nm (Boy et al, 2008;Lampilahti et al, 2021;Meskhidze et al, 2019;Pillai et al, 2013;Pryor et al, 2011;Svenningsson et al, 2008).…”
mentioning
confidence: 99%
“…cm -3 in remote continental, remote marine and forest regions and 10 7 molec. cm -3 in urban and rural agricultural lands using the same technique as in here (Berresheim et al, 2000;Kuang et al, 2008;Petäjä et al, 2009;Kurtén et al, 2011;Zheng et al, 2011;Chen et al, 2012;Jokinen et al, 2012;, Kürten et al, 2014Bianchi et al, 2016;Baalbaki et al, 2021;Dada et al, 2020b). It has been well documented that SA contributes to aerosol formation and growth processes (Boy et al, 2008;Eisele et al, 2006;Fiedler et al, 2005;Iida et al, 2008;Sarnela et al, 2015;Jokinen et al, 2018;Kürten et al, 2015Kürten et al, , 2016Mauldin et al, 2001;Paasonen et al, 2010;Wang et al, 2011;Weber et al, 1998Weber et al, , 1999Yao et al, 2018;Dada et al, 2020b).…”
Section: Precursor Vapor Concentrations and Their Sourcesmentioning
confidence: 99%
“…New particle formation (NPF) and growth of aerosols are regional processes occurring globally introducing a substantial aerosol load into the atmosphere. NPF has been observed in different environments, including pristine (Asmi et al, 2016;Jang et al, 2019;Jokinen et al, 2018), polluted boundary layers and urban areas (Kulmala et al, 2021;Kulmala et al, 2017;Manninen et al, 2010;Kulmala et al, 2016;Wang et al, 2017;Cai and Jiang, 2017;Deng et al, 2020;Yao et al, 2018;Du et al, 2021;Yan et al, 2021), boreal forests (Buenrostro Mazon et al, 2016;Dada et al, 2017;Kulmala et al, 2013;Kyrö et al, 2014;Leino et al, 2016;Nieminen et al, 2014;Rose et al, 2018), tropical forests (Artaxo et al, 2013;Wimmer et al, 2018) and mountain tops (Bianchi et al, 2016(Bianchi et al, , 2020. Few studies have investigated NPF processes in a coastal environment although the coastal NPF research started quite early.…”
Section: Introductionmentioning
confidence: 99%